ESTIMATION OF THERMAL PARAMETERS OF POWER BIPOLAR TRANSISTORS BY THE METHOD OF THERMAL RELAXATION DIFFERENTIAL SPECTROMETRY - V. S. Niss; A. S. Vaskou; A. S. Turtsevich; A. F. Kerentsev; V. K. Kononenko (Приборы и методы измерений, 2015)
Thermal performance of electronic devices determines the stability and reliability of the equipment. This leads to the need for a detailed thermal analysis of semiconductor devices. The goal of the work is evaluation of thermal parameters of high-power bipolar transistors in plastic packages TO-252 and TO-126 by a method of thermal relaxation differential spectrometry. Thermal constants of device elements and distribution structure of thermal resistance defined as discrete and continuous spectra using previously developed relaxation impedance spectrometer. Continuous spectrum, based on higher-order derivatives of the dynamic thermal impedance, follows the model of Foster, and discrete to model of Cauer. The structure of sample thermal resistance is presented in the form of siх-chain electro-thermal RC model. Analysis of the heat flow spreading in the studied structures is carried out on the basis of the concept of thermal diffusivity. For transistor structures the area and distribution of the heat flow cross-section are determined. On the basis of the measurements the thermal parameters of high-power bipolar transistors is evaluated, in particular, the structure of their thermal resistance. For all of the measured samples is obtained that the thermal resistance of the layer planting crystal makes a defining contribution to the internal thermal resistance of transistors. In the transition layer at the border of semiconductor-solder the thermal resistance increases due to changes in the mechanism of heat transfer. Defects in this area in the form of delamination of solder, voids and cracks lead to additional growth of thermal resistance caused by the reduction of the active square of the transition layer. Method of thermal relaxation differential spectrometry allows effectively control the distribution of heat flow in high-power semiconductor devices, which is important for improving the design, improve the quality of landing crystals of power electronics products to reduce overheating.